2022
DOI: 10.1097/dcr.0000000000002528
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Lymph Node Size and Tumor Distance From Anal Verge Accurately Predict Positive Lateral Pelvic Lymph Nodes in Rectal Cancer: A Multi-Institutional Retrospective Cohort Study

Abstract: BACKGROUND: Lateral pelvic lymph node dissection improves oncological outcomes in rectal cancer patients with suspected lateral pelvic lymph node metastasis. However, the indication for this procedure remains unclear. OBJECTIVE: This study aimed to identify the predictive factors for lateral lymph node metastasis and the indications for lateral pelvic lymph node dissection. DESIGN: A multi-institutional retrospective study. SETTINGS: This study was conducted at 3 university hospitals. PATIENTS: This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Selective LLND had a higher pathologic LPNM.A study in Korea 19 selectively performed LLND to patients with clinically suspected LPN metastasis showed that the positive rate was 34.8%. A large multicenter retrospective cohort study in China showd that positive LPN was 23.5% in patients suspected LPN metastasis based on magnetic resonance imaging (MRI) evaluation 20 .…”
Section: Discussionmentioning
confidence: 96%
“…Selective LLND had a higher pathologic LPNM.A study in Korea 19 selectively performed LLND to patients with clinically suspected LPN metastasis showed that the positive rate was 34.8%. A large multicenter retrospective cohort study in China showd that positive LPN was 23.5% in patients suspected LPN metastasis based on magnetic resonance imaging (MRI) evaluation 20 .…”
Section: Discussionmentioning
confidence: 96%
“…It should be noted that this study was preventive dissection and LLND was performed on lateral lymph nodes with images less than 10mm. Another multicenter study from Korea 19 found, LPN short-axis diameter (< 5, 5-<10, and 10 mm) was signi cantly associated with LPN recurrence-free survival (5-year survival rate (5YSR), 98.2, 91.7, and 40.1%, respectively, P < 0.05), locoregional recurrence-free survival (5YSR, 95.5, 87.6, and 40.1%, respectively, P < 0.05), relapse-free survival (5YSR, 76.8, 72.5, and 30.3, respectively, P < 0.05), and overall survival (5YSR, 86.3, 83.0, and 57.5%, respectively, P < 0.05). A multicenter study from China 20 found that the 3-year OS, RFS, and LRFS in the LPN positive group were signi cantly worse than those in the LPN negative group.…”
Section: Discussionmentioning
confidence: 99%
“…The primary method for predicting mLLN is based on the size diagnosis of the maximum short axis diameter (SAD) of the lymph nodes on computed tomography or magnetic resonance imaging (MRI) after NACRT. However, it has recently been suggested that it is more appropriate to use the initial lateral pelvic lymph nodes (LPN) size rather than the post-chemoradiotherapy (CRT) LPN size as a predictor of mLLN, because in clinical practice, there are many cases where CRT is not performed before surgery for various reasons, such as patient rejection, old age, or complication[ 6 ]. Therefore, PLND is advocated as an adjunct to radical surgery for colorectal cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, PLND should be carefully considered for such patients[ 8 ]. Studies from Japan proved that the optimal indications for PLND in rectal cancer are the initial lymph node ≥ 8 mm and the distance between the anus and the tumor edge > 5 cm or the initial lymph node ≥ 6 mm and the distance between the anus and the tumor edge ≤ 5 cm[ 6 , 9 ]. Malakorn et al [ 7 ] showed no evidence of local or distant recurrence of disease after 2 years of follow-up by using minimally invasive robot-assisted PLND to treat patients with persistent lateral pelvic lymph node enlargement after NACRT, which confirmed that Chua et al [ 5 ] The proposed robotic assistance may be a useful aid for PLND.…”
Section: Introductionmentioning
confidence: 99%